The Implementation of Cooperative Learning of Two Stay Two Stray Type through Students’ Reading - Liansari, Vevy; Nuroh, Ermawati Zulikhatin; Destiana, Evie (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2021)
This study aims to determine the effect of the cooperative learning model type Two Stay Two Stray on the reading skills of third-grade students at SD Zainuddin, Waru, Sidoarjo. This study was conducted by using a quantitative approach of Pre-Experimental Design research with a One-Group Post-test-Pre-test design. In this design, there is one group, namely the Experiment class. The results of this study indicated that there is an effect of the cooperative learning model type Two Stay Two Stray on the reading skills of third-grade students at SD Zainuddin, Waru, Sidoarjo. It is evident that the results of the data calculations that have been carried out obtained a significant value of .000 or (.000 < 0.05), or obtained t-count = 43.071 which was then compared with t-table = 1.745, with a significant level of 5% it is known that t-count is greater 43,071 of t-table = 1,745 (t-count > t-table ). Thus, there is an effect of the cooperative learning model type Two Stay Two Stray on the reading skills of third-grade students at SD Zainuddin, Waru, Sidoarjo. This is evident from the results of the calculation of the researcher's hypothesis test with the one-sample t-test. These results are known that Ha is accepted and H0 is rejected with a significant value obtained .000 or (.000 < 0.05).